1986
DOI: 10.1099/0022-1317-67-8-1717
|View full text |Cite
|
Sign up to set email alerts
|

Capsid Polypeptides in a Group III Virus from Gaeumannomyces graminis var. tritici Are Related

Abstract: SUMMARYPeptide mapping and amino acid analysis have shown that the two capsid polypeptides of a group III virus, 87-1-H, from Gaeumannomyces graminis are closely related.Isometric double-stranded RNA (dsRNA) virus particles are common in field isolates of the wheat take-all fungus, Gaeumannomyces graminis var. tritici (Ggt), and have been divided into four groups based on their physical and serological properties and the number and sizes of their dsRNA segments and capsid polypeptides (Buck et al., 1981;McFadd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The group III virus, designated 87-1-H, from Gaeumannomyces graminis (Jamil & Buck, 1986) and the virus from the yeast Yarrowia lipolytica (EI-Sherbeini et al, 1987) have recently been reported to possess two or more related capsid polypeptides of comparable size to those of the 190S virus. The larger of the two capsid polypeptides of G. graminis 87-1-H virus, unlike p88 of H. victoriae 190S virus, appears to convert to the smaller polypeptide when virus preparations are stored at 4 °C for 1 month or longer (Jamil & Buck, 1986).…”
Section: Serological Reactivity Of Capsid Polypeptidesmentioning
confidence: 99%
“…The group III virus, designated 87-1-H, from Gaeumannomyces graminis (Jamil & Buck, 1986) and the virus from the yeast Yarrowia lipolytica (EI-Sherbeini et al, 1987) have recently been reported to possess two or more related capsid polypeptides of comparable size to those of the 190S virus. The larger of the two capsid polypeptides of G. graminis 87-1-H virus, unlike p88 of H. victoriae 190S virus, appears to convert to the smaller polypeptide when virus preparations are stored at 4 °C for 1 month or longer (Jamil & Buck, 1986).…”
Section: Serological Reactivity Of Capsid Polypeptidesmentioning
confidence: 99%